The Effect of Inclusive Leadership and Intrinsic Motivation on Innovation Work Behavior: The Mediating Role of Creative Self-Efficacy - Ananda Karisma Yuliawati; Dahliana Kamener; Fivi Anggraini (Journal of Social Research, 2025)
In today's dynamic and competitive business environment, innovation is a key driver of organizational success. Companies must leverage their human capital to foster creativity and adaptability, particularly in response to rapid technological advancements. However, many organizations face challenges in cultivating innovation work behavior (IWB) among employees, often due to a lack of supportive leadership or intrinsic motivation. This research aims to examine the influence of inclusive leadership and intrinsic motivation on innovation work behavior, mediated by creative self-efficacy, at PT Global Humanity Innovation (GHI). Using a quantitative research method, data were collected through a census survey involving all 61 employees across various divisions. The analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS. The results indicate that both inclusive leadership and intrinsic motivation have a significant positive effect on innovation work behavior. Furthermore, creative self-efficacy significantly mediates the relationship between inclusive leadership and innovation work behavior, as well as between intrinsic motivation and innovation behavior. The study highlights the importance of psychological and leadership-related factors in enhancing employee innovation at GHI. These findings provide practical implications for improving organizational strategies and nurturing a work environment that supports creativity and innovation through leadership inclusiveness and the internal motivation of employees.